Commentary on Genesis - Didymus, the Blind, approximately 313-approximately 398 (Fathers of the church, 2016)
"Blind since early childhood, the Egyptian theologian and monk Didymus (ca. 313-398) wielded a masterful knowledge of Scripture, philosophy, and previous biblical interpretation, earning the esteem of his contemporaries Athanasius, Antony of Egypt, Jerome, Rufinus, and Palladius, as well as the historians Socrates and Theodoret in the decades following his death. Certain features of the Genesis commentary, unfortunately not preserved in its entirety, seem to indicate that it may have been Didymus's earliest work. Not only is he silent in regard to his other works, but remarks on specific heresies as well as christological interpretations occur much less frequently here than in his Zechariah commentary. Moreover, the heavier reliance on Philo and Origen may indicate relative inexperience. Whereas Didymus specifically names Philo in this commentary, he never identifies Origen as one of his sources even when quoting the latter verbatim. Like Origen, he rejects anthropomorphic interpretations and proceeds to an allegorical approach when the literal meaning repels him. He does not, however, neglect the literal-historical level; see, for example, his examination of the story of the Flood. All three of Origen's levels of interpretation--literal, moral, and allegorical--are mobilized here. This previously untranslated text is crucial for studies of the fourth century and of the monumental influence of Origen."